Singapore Inflation Expectations: Expecting the Unexpected - GHOSH, Aurobindo (Institutional Knowledge at Singapore Management University, 2012)
The study of inflation expectations of Singapore house-holds is a multi-disciplinary industry-relevant research that comes out of a partnership between Singapore Management University (SMU) and MasterCard. The research team for this MasterCard-SKBI Singapore Index of Inflation Expectations (SInDEx) project applied rigorous methods using current internet-based marketing survey tools for data-collection and advanced econometric techniques to analyse the data. The updates from the quarterly waves are keenly followed by policymakers, market watchers and the media because of the enormous importance of cost of living to individuals and businesses alike.